Studies on the Effect of Different Colour Attractants on Cross-pollination in Boswellia serrata Roxb. Ex Colebr. - Sharma, Manoj Kumar; Kshetrapal, Shashikala; Ahuja, Kapil (Indian Forester, 1999)
The present investigation deals with the effect of different colours as pollinator attractants on cross-pollination in Boswellia serrata. Among red, blue, green, pink, yellow, black and white attractants, pink, red and blue colour were found to be superior to attract the maximum number of pollinators and cross-pollination percentage was maldmum. Response of pollinators to black and green colour in respect for cross-pollination was observed to be very poor than the control.